Intraspecific Variation in Responses of a Montane Grass, Festuca thurberi, to Simulated Biological Invasion - Trautwig, Adam N.; Cousins, Elsa A.; Stinson, Kristina A. (Frontiers in Forests and Global Change, 2022)
High elevation plant populations, such as those found in sub-alpine meadows, are at the forefront of climate change and likely to experience novel interactions with migrating plants from lower elevations, including non-native species. Some of these non-native plants, particularly members of the Brassicaceae, produce secondary metabolites that have been shown to inhibit root fungi in other ecosystems. We conducted a growth experiment with plant leachates in order to evaluate the degree to which the dominant high elevation grass species, Festuca thurberi would be affected by future novel interactions with the non-native mustard, Thlaspi arvense, relative to a native mustard (Noccaea fendleri). We assessed growth, chlorophyll content, biomass, mortality, and percent colonization of arbuscular mycorrhizal fungi (AMF) and dark septate endophytes (DSE) in different genotypes of F. thurberi exposed to leachates from native and non-native mustards as well as F. thurberi leachate and a deionized (DI) water control. New growth and mortality varied more by genotype than by treatment with leachate of F. thurberi, T. arvense, and N. fendleri. Treatment, genotype, and the treatment x genotype interaction all had significant effects on chlorophyll content, with N. fendleri treatments demonstrating higher relative greenness levels than control treatments. Percent of fine roots with dark septate endophytes was significantly affected by individual genotype and treatment x genotype interaction, but there were no effects of treatment, genotype, or their interaction on percent root colonization by arbuscules or vesicles. Overall, we show that performance of a dominant high-altitude grass species varies in its response to the presence of an expanding, non-native plant, which may become increasingly common due to climate change.